Implementation of Cattle Grazing Positions for Determining Cardinal Directions and the Qibla Direction - Ardana Ash Siddiqi; Friska Linia Sari (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
Cows grazing facing north or south is a unique fact that not everyone knows. Therefore, this needs to be studied as an addition to the scientific treasures of science, especially in the field of falak science, this can be related to one of the fields in falak science, namely Qibla direction. This research aims to reveal the truth that the cow's body faces North South so that later it can be used to determine the Qibla direction. The results showed that the method of determining the Qibla direction with the position of grazing cows is done by observation repeatedly in order to produce accurate results. After doing the research, it is true that the position of the cow when grazing exposes its body to the North or South so that this method can be used to determine the Qibla direction. However, there are still many shortcomings when using this method so there is still a need for in-depth research on cows. There is another unique thing, it turns out that it is not only cows that do the behavior of directing their bodies to North and South when grazing, there are other animals such as buffaloes, sheep, deer.